Penyuluhan Ketahanan Keluarga dalam Perspektif Kampung Ramah Keluarga Kasus di Desa Ciherang, Kecamatan Dramaga, Kabupaten Bogor - Euis Sunarti; Defina Defina; Risda Rizkillah; Musthofa Musthofa (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
Family is the smallest unit of society. Family resilience must be increased to realize family prosperity. Family resilience cannot be separated from the environment as it is a family friendly village. This family friendly village can be realized through a programme that includes family resilience education. One way to develop a family is through counseling about family resilience and the role of the family in creating a family friendly environment. This activity aims to increase the family’s understanding of the development and function of the family in realizing family resilience by developing a Family Friendly Village Model in Ciherang Village, Dramaga District, Bogor Regency, West Java Province. Productive-age mothers participated in this outreach activity. Counseling was performed thrice (March-May 2024). The first activity was offline counselling/education regarding the definition, components, and scope of family resilience. The second activity is counseling and education regarding the stages and tasks of family development. The third activity is counselling/education related to strengthening the understanding of family resilience. Based on the pre-test results, it was discovered that the participants did not know or understand the stages of family development, function, and resilience. However, after counseling and post-test, it was discovered that the participants could analyze each family's stages of family development and identify basic tasks, developmental tasks, and crisis tasks that needed to be carried out to increase family resilience. In conclusion, counseling is needed for families to increase their knowledge and understanding of family function and development and to create family resilience.